(untitled) (Research, Society and Development, 2022)
Given the technological-scientific advances, the patient’s demand for more exams and greater availability and functionality of imaging methods, in addition to the aging and clinical complexity of the population, there has been and continues to be significant growth in diagnostic imaging exams and services in last decades. There is a lack of standardization of radiology teaching in institutions, pointing to the need to reassess medical curricula to ensure the rational, conscious and effective use of imaging resources, with benefits for the physician, the patient and the health system. Thus, we sought to assess the level of knowledge of primary care physicians and internal medicine residents about imaging tests as well as their rational use through the correct indication of the methods in clinical situations of daily practice. The study was carried out with 123 physicians, members of primary health care and/or residents of a medical clinic in São Luis, MA, through a structured questionnaire containing questions about general knowledge and an indication of imaging methods. In general, there was a higher level of knowledge expressed by the mean percentage of correct answers (%m.a) among the group of resident physicians (%m.a= 85.7 ±6.4) when compared to AB doctors (%m.a=78.2 ±15), with less time since graduation (%m.a=83.35±11.1). Physicians working in emergency services (84.70±7%) had higher means. Although AB physicians have had good results in recommending imaging tests in specific situations, in most cases the residents.